P '2-phase sodium-electrode layered transition metal oxide positive electrode material as well as preparation method and application thereof

By adding titanium elements to the preparation of P'2 phase NaxMO2 and controlling the content of sodium and titanium, the P'2 phase sodium electro-layer transition metal oxide positive electrode material is synthesized without quenching, solving the problems of large energy consumption and environmental protection in the prior art, and improving electrochemical performance and production efficiency.

CN119612595AActive Publication Date: 2025-03-14WUXI ANNA ENERGY TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411820907.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-14
Estimated Expiration
2044-12-11

AI Technical Summary

Technical Problem

In the preparation of P'2 phase NaxMO2, the existing P'2 phase requires quenching treatment at a condition exceeding 1000°C, resulting in large energy consumption, low production efficiency, high cost and unenvironmental protection.

Method used

By adding titanium elements to the raw material and controlling the content of sodium and titanium, a sodium-electric layered transition metal oxide positive electrode material of P'2 phase is obtained by a one-step sintering method without quenching.

Benefits of technology

It reduces synthetic energy consumption, improves production efficiency, reduces costs, and reduces environmental pollution. At the same time, the electrochemical performance of the materials has also been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119612595A_ABST
    Figure CN119612595A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a P '2-phase sodium-electrode layered transition metal oxide positive electrode material, which comprises the following steps: by taking a transition metal source and a sodium source as raw materials, carrying out ball milling and uniform mixing, carrying out heat treatment in an air atmosphere, and carrying out furnace cooling to obtain the sodium-electrode layered transition metal oxide positive electrode material, wherein the sodium electrode layered transition metal oxide positive electrode material has a P '2 phase, the chemical general formula is NaxTiyMn1-yO2, x and y are molar ratios, x is more than or equal to 1.1 and less than 1.7, and y is more than or equal to 0.14 and less than 0.22. According to the method disclosed by the invention, the P '2-phase sodium electric layered transition metal oxide positive electrode material is obtained under the condition of not needing quenching by adding the titanium element and combining and controlling the contents of sodium and titanium, and the obtained positive electrode material has excellent electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion battery positive electrode materials, and in particular to a P'2 phase sodium battery layered transition metal oxide positive electrode material and a preparation method and application thereof. Background Art

[0002] Layered transition metal oxides Na x MO2 (M is a transition metal element) mainly includes O3 and P2 type layered transition metal oxides. x The MO2 system includes two types: P2 phase and P'2 phase. Compared with the P2 phase, the P'2 phase has no manganese vacancies, the overall structure is more highly ordered, and the electrochemical performance is better.

[0003] P2- and P'2 phase Na x The difference between MO2 lies mainly in the synthesis conditions, and the heating process is one of the factors. x MO2 is obtained by quenching at over 1000℃ so that there is no manganese vacancy in the P'2 phase structure, and the P2 phase Na x The synthesis of MO2 requires slow cooling after heating to 900°C. During the cooling process, the charge of the material becomes unbalanced due to the continuous addition of oxygen in the air to the bulk phase of the material. In order to balance the charge, the P2 phase Na x The MnIII in MO2 tends to MnIV, which leads to the generation of vacancies in the Mn layer.

[0004] The quenched P'2 phase Na x MO2 avoids the above situation, so there is no manganese vacancy in the P'2 phase structure, and the overall structure is more highly ordered. However, the sintering process uses quenching (>1000℃) to consume a lot of energy, which affects production efficiency, is costly, and is not environmentally friendly. Summary of the invention

[0005] The present invention aims to prepare P'2 phase Na x The invention discloses a method for preparing a P'2 phase sodium layered transition metal oxide positive electrode material, wherein the P'2 phase sodium layered transition metal oxide positive electrode material is obtained by adding titanium and controlling the content of sodium and titanium without quenching. x MO2, the obtained positive electrode material has excellent electrochemical properties.

[0006] According to a first aspect of the present invention, there is provided a method for preparing a P'2 phase sodium-electrode layered transition metal oxide positive electrode material, comprising the following steps:

[0007] A transition metal source and a sodium source are used as raw materials, ball-milled and mixed evenly, and then heat-treated in an air atmosphere and then cooled in a furnace to obtain a sodium-electrolyte layered transition metal oxide positive electrode material;

[0008] The sodium layered transition metal oxide positive electrode material has a P'2 phase and a chemical formula of Na x Ti y Mn 1- y O2, x, y are molar ratios, 1.1≤x<1.7, 0.14≤y<0.22;

[0009] By adding titanium and controlling the content of sodium and titanium, a P'2 phase sodium-electrolyte layered transition metal oxide positive electrode material is obtained without the need for quenching.

[0010] As an optional embodiment, the masses of the transition metal source and the sodium source are formulated according to the stoichiometric ratio of the sodium-electrolyte layered transition metal oxide positive electrode material.

[0011] As an optional embodiment, in the transition metal source, the corresponding transition metal ions are Ti and Mn.

[0012] As an optional embodiment, the transition metal source includes a transition metal salt, a transition metal oxide or a transition metal hydroxide; the transition metal salt includes a carbonate, acetate, nitrate, chloride, sulfate, borate or phosphate of a transition metal.

[0013] As an optional embodiment, the sodium source includes one or more of sodium carbonate, sodium nitrate, sodium sulfate, sodium phosphate, sodium fluoride, sodium iodide, sodium oxalate and sodium hydroxide.

[0014] As an optional embodiment, the heat treatment conditions are: heat treatment at 1000±10°C for 15 to 18 hours.

[0015] According to a second aspect of the present invention, there is provided a P'2 phase sodium electrode layered transition metal oxide positive electrode material prepared by the above method.

[0016] As an optional embodiment, the bulk phase of the positive electrode material is a sodium layered transition metal oxide Na x Ti y Mn 1- y O2, the bulk phase has no transition metal offset or vacancy; the sodium layered transition metal oxide Na x Ti y Mn 1-y O2 is a P'2 phase, wherein x and y are molar ratios, 1.1≤x<1.7, 0.14≤y<0.22.

[0017] According to a third aspect of the present invention, there is provided a use of the aforementioned P'2 phase sodium-electrode layered transition metal oxide positive electrode material in a sodium-ion battery.

[0018] According to a fourth aspect of the present invention, a sodium ion battery is provided, which uses the above-mentioned P'2 phase sodium-ion layered transition metal oxide positive electrode material as a positive electrode material.

[0019] From the above technical solutions of the present invention, it can be seen that the preparation method of the P'2 phase sodium layered transition metal oxide positive electrode material proposed in the present invention is x Titanium is introduced into MnO2, and the contents of titanium and sodium are controlled. Through a one-step sintering method, a P'2 phase sodium layered transition metal oxide positive electrode material is obtained without quenching.

[0020] By setting specific high sodium conditions, we can prevent sodium loss during furnace cooling and manganese vacancies caused by charge imbalance due to the continuous replenishment of oxygen in the air. On this basis, by introducing a specific range of titanium elements, a fluxing effect is achieved, which reduces the difficulty of the sintering process and allows the body phase to evolve into a pure P'2 phase without quenching, thereby reducing synthesis energy consumption, improving production efficiency, reducing costs, and reducing pollution to the environment.

[0021] The sodium-electrolyte layered transition metal oxide positive electrode material prepared by the method of the present invention suppresses the Jan-Taylor distortion of manganese by adding titanium elements in a specific range, reduces the phase change during the cycle process, and makes the structure of the material more stable during the cycle process, so that the final positive electrode material exhibits better cycle performance; and by controlling the range of sodium, the first efficiency and capacity of the material are improved while avoiding the appearance of residual alkali on the surface of the material; thus, it is ensured that the material has excellent electrochemical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is the XRD spectra of the samples prepared in Examples 1-8 of the present invention and Comparative Example 1.

[0023] Figure 2 It is the SEM spectra of the samples prepared in Examples 1-8 of the present invention and Comparative Example 1.

[0024] Figure 3 It is the first cycle charge and discharge diagram of the samples prepared in Examples 1-8 of the present invention and Comparative Example 1 at a current density of 0.01 A / g.

[0025] Figure 4 The graphs are of Examples 1-8 and the samples prepared in Comparative Example 1 at 300 cycles at a current density of 0.1 A / g. DETAILED DESCRIPTION

[0026] In order to better understand the technical content of the present invention, specific embodiments are given and described as follows in conjunction with the accompanying drawings.

[0027] Various aspects of the present invention are described in this disclosure with reference to the accompanying drawings, in which many illustrative embodiments are shown. The embodiments of the present disclosure are not necessarily intended to include all aspects of the present invention. It should be understood that the various concepts and embodiments introduced above, as well as those described in more detail below, can be implemented in any of many ways.

[0028] As a manganese-based material, the P'2 phase still has the inherent intrinsic defects of manganese-based materials, and there is still much room for improvement in its electrochemical performance.

[0029] Cationic modification is a common material modification method, but the cationic modified materials reported so far still have some deficiencies in electrochemical performance and sintering process. For example, the P'2 phase material Na after ion modification of copper 0.65 Mn 0.9 Cu 0.1 O2 (Yuexia Ling, 2021, 13, 58665), can increase the material cycle from 55% to 75% at 1C, but the capacity is reduced by ~60mAh / g; for example, the P'2 phase material Na2O2 modified with nickel ions and iron ions 0.67 [Ni 0.1 Fe 0.1 Mn 0.8 ]O2 (Ji Ung Choi, 2020, 10, 2001346), can still maintain 80% capacity retention after 200 cycles at 3C, but there is also a significant decrease in capacity.

[0030] Furthermore, these methods all require the use of P'2 phase materials obtained by quenching at temperatures above 1000°C, which consumes a lot of energy.

[0031] Therefore, the present invention designs a method for preparing a positive electrode material for a sodium ion battery, and synthesizes a sodium-ion battery layered transition metal oxide with a P'2 phase without quenching treatment, which can effectively improve energy consumption; the obtained P'2 phase sodium-ion battery layered transition metal oxide is modified by titanium ions, which inhibits problems such as phase change during the cycle, and has the advantages of high initial efficiency and long cycle life.

[0032] In an exemplary embodiment of the present invention, a method for preparing a P'2 phase sodium-electrode layered transition metal oxide positive electrode material is provided, comprising the following steps:

[0033] A transition metal source and a sodium source are used as raw materials, ball-milled and mixed evenly, and then heat-treated in an air atmosphere and then cooled in a furnace to obtain a sodium-electrolyte layered transition metal oxide positive electrode material;

[0034] The sodium layered transition metal oxide positive electrode material has a P'2 phase and a chemical formula of Na x Ti y Mn 1- y O2, x, y are molar ratios, 1.1≤x<1.7, 0.14≤y<0.22;

[0035] By adding titanium and controlling the content of sodium and titanium, a P'2 phase sodium-electrolyte layered transition metal oxide positive electrode material is obtained without the need for quenching.

[0036] As an optional example, the masses of the transition metal source and the sodium source are formulated according to the stoichiometric ratio of the sodium-electrolyte layered transition metal oxide positive electrode material.

[0037] As an optional example, in the transition metal source, the corresponding transition metal ions are Ti and Mn.

[0038] As optional examples, the transition metal source includes a transition metal salt, a transition metal oxide or a transition metal hydroxide; the transition metal salt includes a carbonate, acetate, nitrate, chloride, sulfate, borate or phosphate of a transition metal.

[0039] As optional examples, the sodium source includes one or more of sodium carbonate, sodium nitrate, sodium sulfate, sodium phosphate, sodium fluoride, sodium iodide, sodium oxalate, and sodium hydroxide.

[0040] As an optional example, the heat treatment condition is: heat treatment at 1000±10°C for 15 to 18 hours.

[0041] In another exemplary embodiment of the present invention, a P'2 phase sodium-electrode layered transition metal oxide positive electrode material prepared by the above method is provided.

[0042] As an optional example, the bulk phase of the positive electrode material is a sodium layered transition metal oxide Na x Ti y Mn 1-y O2, the bulk phase has no transition metal offset or vacancy; the sodium layered transition metal oxide Na x Ti y Mn 1-y O2 is a P'2 phase, wherein x and y are molar ratios, 1.1≤x<1.7, 0.14≤y<0.22.

[0043] In another exemplary embodiment of the present invention, there is provided a use of the aforementioned P'2 phase sodium-electrode layered transition metal oxide positive electrode material in a sodium-ion battery.

[0044] In another exemplary embodiment of the present invention, a sodium ion battery is provided, which uses the aforementioned P'2 phase sodium-electrolyte layered transition metal oxide positive electrode material as a positive electrode material, and the sodium ion battery exhibits excellent rate performance and cycle stability.

[0045] For better understanding, the present invention is further described below in conjunction with several specific examples, but the preparation process is not limited thereto, and the content of the present invention is not limited thereto.

[0046] Unless otherwise specified, the materials in the examples were prepared according to existing methods or directly purchased from the market.

[0047] Example 1

[0048] Set 0.1 mol Na 1.1 Ti 0.06 Mn 0.94 O2, Mn2O3, TiO2, Na2CO3 in a molar ratio of Na:Ti:Mn=1.1:0.06:0.94 (wherein the Na source is 2% excess, i.e. 1.1×(1+0.02)) were ball milled (400r / min, 6h) and mixed evenly, and then heated at 1000℃ for 15h and cooled in the furnace to obtain Na 1.1 Ti 0.06 Mn 0.94 O2 is used as the positive electrode material.

[0049] Example 2

[0050] Set 0.1 mol Na 1.1 Ti 0.10 Mn 0.90 O2, Mn2O3, TiO2, Na2CO3 in a molar ratio of Na:Ti:Mn=1.1:0.10:0.90 (wherein the Na source is 2% excess) were ball milled (400r / min, 6h) and mixed evenly, and then heated at 1000℃ for 15h and cooled in the furnace to obtain Na 1.1 Ti 0.10 Mn 0.90 O2 is used as the positive electrode material.

[0051] Example 3

[0052] Set 0.1 mol Na 1.1 Ti 0.14 Mn 0.86O2, Mn2O3, TiO2, Na2CO3 in the molar ratio of Na:Ti:Mn = 1.1:0.14:0.86 (wherein the Na source is 2% excess) are ball milled (400r / min, 6h) and mixed evenly, and then heated at 1000℃ for 15h and cooled in the furnace to obtain Na 1.1 Ti 0.14 Mn 0.86 O2 is used as the positive electrode material.

[0053] Example 4

[0054] Set 0.1 mol Na 1.1 Ti 0.18 Mn 0.82 O2, Mn2O3, TiO2, Na2CO3 in a molar ratio of Na:Ti:Mn=1.1:0.18:0.82 (wherein the Na source is 2% excess) were ball milled (400r / min, 6h) and mixed evenly, and then heated at 1000℃ for 15h and cooled in the furnace to obtain Na 1.1 Ti 0.18 Mn 0.82 O2 is used as the positive electrode material.

[0055] Example 5

[0056] Set 0.1 mol Na 1.1 Ti 0.22 Mn 0.78 O2, Mn2O3, TiO2, Na2CO3 in a molar ratio of Na:Ti:Mn=1.1:0.22:0.78 (wherein the Na source is 2% excess) were ball milled (400r / min, 6h) and mixed evenly, and then heated at 1000℃ for 15h and cooled in the furnace to obtain Na 1.1 Ti 0.22 Mn 0.78 As positive electrode material.

[0057] Example 6

[0058] Set 0.1 mol Na 0.8 Ti 0.18 Mn 0.82 O2, Mn2O3, TiO2, Na2CO3 in a molar ratio of Na:Ti:Mn=0.8:0.18:0.82 (wherein the Na source is 2% excess) are ball milled (400r / min, 6h) and mixed evenly, and then heated at 1000℃ for 15h and cooled in the furnace to obtain Na 0.8 Ti 0.18 Mn 0.82 O2 is used as the positive electrode material.

[0059] Example 7

[0060] Set 0.1 mol Na 1.4 Ti 0.18 Mn 0.82 O2, Mn2O3, TiO2, Na2CO3 in a molar ratio of Na:Ti:Mn=1.4:0.18:0.82 (wherein the Na source is 2% excess) are ball milled (400r / min, 6h) and mixed evenly, and then heated at 1000℃ for 15h and cooled in the furnace to obtain Na 1.4 Ti 0.18 Mn 0.82 O2 is used as the positive electrode material.

[0061] Example 8

[0062] Set 0.1 mol Na 1.7 Ti 0.18 Mn 0.82 O2, Mn2O3, TiO2, Na2CO3 in a molar ratio of Na:Ti:Mn=1.7:0.15:0.85 (wherein the Na source is 2% excess) were ball milled (400r / min, 6h) and mixed evenly, and then heated at 1000℃ for 15h and cooled in the furnace to obtain Na 1.7 Ti 0.18 Mn 0.82 O2 is used as the positive electrode material.

[0063] Comparative Example 1

[0064] Set 0.1 mol Na 0.67 Ti 0.18 Mn 0.82 O2, Mn2O3, TiO2, and Na2CO3 were mixed evenly by ball milling (400r / min, 6h) at a molar ratio of Na:Ti:Mn=0.67:0.18:0.82 (wherein the Na source was 2% excess), and then heated at 1000°C for 15h and quenched to obtain Na 0.67 Ti 0.18 Mn 0.82 O2 is used as the positive electrode material.

[0065] XRD

[0066] The materials obtained in Examples 1-8 and Comparative Example 1 were subjected to XRD testing, and the results are as follows: Figure 1 shown.

[0067] It can be seen from the figure that the samples of comparative example 1, embodiments 3, 4 and 7 are pure P'2 phase, and impurities exist in the physical phases of other embodiments, which proves that the bulk phase of the positive electrode material obtained by the method of the present invention is mainly composed of P'2 phase, and the pure phase can be synthesized only when the sodium content x is controlled to be 1.1≤x<1.7 and the titanium content y is controlled to be 0.14≤y<0.22.

[0068] SEM

[0069] The materials obtained in Examples 1-8 and Comparative Example 1 were subjected to SEM testing, and the results are as follows: Figure 2 shown.

[0070] It can be seen from the SEM image that the samples of the comparative example and the embodiment are all irregular plate-like morphology, and as the titanium content increases, the plate-like morphology becomes more prominent and the size becomes more uniform. In addition, as the titanium content increases, the plate-like size also increases. At the same time, as the sodium content increases, more small particles appear on the sample surface, which indicates that residual alkali sodium carbonate is generated on the surface. Therefore, a certain amount of sodium content and titanium content are required to synthesize pure P'2 phase to ensure the final electrochemical performance.

[0071] It can be proved from the above that the present invention successfully synthesizes the P'2 phase sodium-electrode layered transition metal oxide without quenching, and introduces titanium element into the transition metal layer to further improve its performance.

[0072] Preparation of electrodes and testing of their electrochemical properties

[0073] The prepared positive electrode material is uniformly mixed with superconducting carbon black (Super P) and polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1, dissolved in N-methylpyrrolidone (NMP), and coated on the surface of aluminum foil, and then dried in a vacuum oven at 80°C for 10 hours to obtain a P'2 phase layered transition metal oxide electrode.

[0074] A P'2 phase layered transition metal oxide electrode was used as the positive electrode, a sodium metal sheet as the negative electrode, and 1.0 mol / LNaPF6 / propylene carbonate as the electrolyte. A half-cell was assembled in a glove box with an argon atmosphere. The electrochemical properties of the surface-coated layered transition metal oxide electrode material were tested, including specific capacity, rate performance, cycle stability and first coulombic efficiency. The test voltage range was 2 to 4.3 V.

[0075] The test results are shown in Table 1 and Figure 3-4 shown.

[0076] Table 1

[0077]

[0078] Combination Figure 3-4 As can be seen from Table 1, the initial efficiency, capacity and cycle of the material obtained without quenching treatment are closely related to the sodium content and titanium content, as well as the purity of the phase; the overall performance of the pure phase material is better than the electrochemical performance of the multi-phase material (Examples 3, 4 and 7 compared with Examples 1-2, 5-6 and 8); and as the titanium content increases, the cyclic stability of the material will be better; as the sodium content increases, the initial efficiency of the material will be higher.

[0079] The first efficiency, capacity and cycle of the pure P'2 synthesized without quenching were significantly improved compared with the material obtained by quenching (Comparative Example 1 and Example 7), the first efficiency was improved by ~10%, and the specific capacity was as high as 213.2 mAh / g (such as Figure 3 After 300 cycles, there is still a cycle retention rate of 81.3% (as shown in Figure 4 shown).

[0080] It can be seen from the test results of the comparative examples and the embodiments that the introduction of an appropriate amount of titanium element has the effect of a flux, and the material will develop into a pure P'2 phase without quenching, and can also inhibit the migration of transition metals, thereby greatly improving the structural stability of the material and making the material have better cycle performance; if the titanium content is too low, the pure P'2 phase cannot be obtained, and if the titanium content is too high, too much titanium cannot enter the transition metal layer, titanium oxide impurities are easily generated, and the morphology cannot reach an ideal state, thereby affecting the electrochemical properties of the material;

[0081] If the sodium content is too low, pure P'2 phase cannot be obtained; if the sodium content increases, the initial efficiency of the material will be higher and the capacity of the material can be increased; if the sodium content is too high, impurities will appear and residual alkali will appear on the surface of the material, making the electrochemical performance of the material worse;

[0082] Therefore, when the titanium addition amount is 0.18 and the sodium addition amount is 1.4, the physical phase at this time is pure P'2 phase, and the electrochemical performance at this time is the best; when the titanium addition amount and the sodium addition amount continue to decrease or increase, impurity phases are likely to appear, and residual alkali appears on the surface of the material, which makes the electrochemical performance of the material deteriorate.

[0083] It can be seen from the above that the method of the present invention can synthesize sodium-electrolyte layered transition metal oxides with P'2 phase without quenching treatment, effectively improve energy consumption, inhibit phase change during cycling, and make the battery show better first efficiency, capacity and cycle.

[0084] Although the present invention has been disclosed as above with preferred embodiments, it is not intended to limit the present invention. A person with ordinary knowledge in the technical field to which the present invention belongs may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be determined by the definition of the claims.

Claims

1. A method for preparing a P'2 phase sodium layered transition metal oxide positive electrode material, characterized in that: The following steps are involved: A transition metal source and a sodium source are used as raw materials, ball-milled and mixed evenly, and then heat-treated in an air atmosphere and then cooled in a furnace to obtain a sodium-electrolyte layered transition metal oxide positive electrode material; The sodium layered transition metal oxide positive electrode material has a P'2 phase and a chemical formula of Na x Ti y Mn 1-y O2, x, y are molar ratios, 1.1≤x<1.7, 0.14≤y<0.22; By adding titanium and controlling the content of sodium and titanium, a P'2 phase sodium-electrolyte layered transition metal oxide positive electrode material is obtained without the need for quenching.

2. The preparation method according to claim 1, characterized in that: The masses of the transition metal source and the sodium source are prepared according to the stoichiometric ratio of the sodium-electrolyte layered transition metal oxide positive electrode material.

3. The preparation method according to claim 1, characterized in that: In the transition metal source, the corresponding transition metals are Ti and Mn.

4. The preparation method according to claim 1, characterized in that: The transition metal source includes a transition metal salt, a transition metal oxide or a transition metal hydroxide; the transition metal salt includes a carbonate, an acetate, a nitrate, a chloride, a sulfate, a borate or a phosphate of a transition metal.

5. The preparation method according to claim 1, characterized in that: The sodium source includes one or more of sodium carbonate, sodium nitrate, sodium sulfate, sodium phosphate, sodium fluoride, sodium iodide, sodium oxalate and sodium hydroxide.

6. The preparation method according to claim 1, characterized in that: The heat treatment conditions are: heat treatment at 1000±10℃ for 15 to 18 hours.

7. A P'2 phase sodium layered transition metal oxide positive electrode material prepared by the method according to any one of claims 1 to 6.

8. The P'2 phase sodium layered transition metal oxide positive electrode material according to claim 7, characterized in that: The bulk phase of the positive electrode material is a sodium layered transition metal oxide Na x Ti y Mn 1-y O2, the bulk phase has no transition metal offset or vacancy; the sodium layered transition metal oxide Na x Ti y Mn 1-y O2 is a P'2 phase, wherein x and y are molar ratios, 1.1≤x<1.7, 0.14≤y<0.

22.

9. Use of the P'2 phase sodium layered transition metal oxide positive electrode material according to any one of claims 7 to 8 in a sodium ion battery.

10. A sodium ion battery, characterized in that: The P'2 phase sodium layered transition metal oxide positive electrode material described in any one of claims 7 to 8 is used as the positive electrode material.

Citation Information

Patent Citations

  • Monoclinic phase sodium manganate material and preparation method thereof

    CN117497741A

  • Sodium manganate positive electrode material and preparation method and application thereof

    CN117878307A

  • Surface-coated high-voltage sodium ion battery positive electrode material and preparation method thereof

    CN119008906A

  • Positive electrode material of sodium-ion battery, and sodium-ion battery

    WO2024217295A1

  • KR20240098668A